STUDI MODEL KONSEPTUAl MENGURANGI KEMISKINAN MELALUI KOPERASI (STUDY OF THE CONCEPTUAL MODEL TO POVERTY ALLEVIATON THROUGH COOPERATIVES) - Sudjatmoko, Agung (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
Cooperatives are business actors who have different identities from other business actors, aiming at thewelfare of members, ensuring fair equity in the control of economic resources, increasing productivity andparticipation of members in cooperatives. The purpose of this study is to develop the concept of reducing povertythrough cooperatives. The method used is a conceptual method that conveys the author's position on a professionalissue. The results of this study are that cooperatives are the right model for reducing poverty, because membership isopen, businesses are carried out jointly to meet common interests, and profit sharing is based on member transactionswith cooperatives. Independence of cooperatives must be built in order to optimize the internal potential in providingbusiness services to its members. Building member trust through economic education on cooperatives is the key toincreasing participation and responsibility with members developing their cooperatives.